The intellectual landscape in the works of J.M. Coetzee - Mehigan, Tim.; Moser, Christian (Woodbridge : Boydell & Brewer Ltd., 2017)
J.M. Coetzee, arguably the most decorated and critically acclaimed writer of fiction in English today, is a deeply intellectual and philosophical writer. Yet while just about everyone who comes to Coetzee's writing is aware that the visible superstructure of his works is moved from below by a vast substructure of ideas, we are still far from grasping Coetzee's intellectual allegiances as a whole. This book sets out to examine those allegiances in a way that has not been done before, bringing together leading scholars in the philosophy of literary fiction and in Coetzee studies. The book is organized into three parts: the first argues that Coetzee's writing sets out a comprehensive ethical trajectory that may be understood as describing a movement in ideas from "I" to "you." The second part considers the problem of language in which the ethical trajectory is rooted and on which it depends. The chapters of the final part proceed from an awareness of the status of literature in the world and concludes by assessing whether Coetzee's fiction attempts to construct a notion of "the neutral" and thereby a new conception of the value of the literary experience in general.
Print version record.
JSTOR
Keywords: Coetzee, J. M., -- 1940- -- Criticism and interpretation; Coetzee, J. M., -- 1940-; LITERARY CRITICISM -- African; Criticism, interpretation, etc